La Prisión Preventiva y su incidencia en el Hacinamiento Carcelario en el Ecuador desde el año 2018 al 2021 - Figueroa Salazar, Melanny Guissele (2023)
The overcrowding in Ecuadorian prisons has reached its highest level in decades, mostly due to inadequate pretrial detention, becoming one of the biggest social problems of our time. Specifically, the present research explores whether prison overcrowding is caused as a consequence of pretrial detention by justice administrators. Several interviews with judges and prosecutors were conducted in order to demonstrate this point, as well as statistical data collected from the National Service of Integral Attention to Adult Deprived of Liberty and Adolescent Offenders in order to obtain the real figures of the number of inmates in the penitentiary centers, as well as their legal situation and the overcrowding in the facilities. As a result, it was found that there is a deliberate application of pretrial detention by justice operators, since there is no due observance of the principles of due process, causing prisons to be overcrowded, largely due to what is known as prisoners without a sentence. Key words: Preventive Detention, Prison Overcrowding, Precautionary Measures, Administration of Justice.